More Accurate Modelling of Digital Subscriber Lines with Inhomogeneity - Jiri Vodrazka; Petr Jares; Boris Simak (Communications - Scientific letters of the University of Zilina, 2013)
The digital subscriber lines are still base of access network to provide Internet connectivity to the public. The transmission capacity is continually increased and performance of digital subscriber lines must be estimated for network provider use. This paper describes two ways for correction of digital subscriber line modelling. The resulting bitrates are calculated with respect to the length of the line and the number of disturbance sources. The article brings new ideas for simulations and calculations of transmission function for line with inhomogeneity and calculations new value of code gain.